2021
DOI: 10.3390/cancers13081871
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting FAK–Paxillin Interaction Reduces Migration and Invadopodia-Mediated Matrix Degradation in Metastatic Melanoma Cells

Abstract: The nonreceptor tyrosine kinase FAK is a promising target for solid tumor treatment because it promotes invasion, tumor progression, and drug resistance when overexpressed. Investigating the role of FAK in human melanoma cells, we found that both in situ and metastatic melanoma cells strongly express FAK, where it controls tumor cells’ invasiveness by regulating focal adhesion-mediated cell motility. Inhibiting FAK in human metastatic melanoma cells with either siRNA or a small inhibitor targeting the kinase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The expression of p-FAK (Tyr397) and p-Src (Tyr416) protein was suppressed in Western blot ( Figure 6 ). Previous studies showed that melanoma cells might be hindered in accelerating invadopodia activity, and subsequently, Vimentin was suppressed ( Liu and Feng, 2010 ; Nagathihalli and Merchant, 2012 ; Mousson et al, 2021 ). Involvement in regulating melanocyte proliferation, β-catenin is most likely associated with the activation of MITF expression ( Larue and Delmas, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of p-FAK (Tyr397) and p-Src (Tyr416) protein was suppressed in Western blot ( Figure 6 ). Previous studies showed that melanoma cells might be hindered in accelerating invadopodia activity, and subsequently, Vimentin was suppressed ( Liu and Feng, 2010 ; Nagathihalli and Merchant, 2012 ; Mousson et al, 2021 ). Involvement in regulating melanocyte proliferation, β-catenin is most likely associated with the activation of MITF expression ( Larue and Delmas, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that tyrosine phosphorylation regulates focal contact assembly and can occur rapidly ( Parsons, 2003 ). Using the FAK mutation at Tyr397, a binding site for Src, the study verified that while downregulating cell migration, this mutation releases a pool of active Src that modulates enhanced invadopodia activity ( Mousson et al, 2021 ). Inhibition of the FAK/Src interaction enhances the proteolytic activity of invasive melanoma cells ( Mousson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Relevant to RHAMM is that ERK1/2 regulates the association between FAK and paxillin, a focal adhesion (FA) adaptor protein, by ensuring a phosphorylation/dephosphorylation feedback loop that influences FA assembly and disassembly during cell migration ( 46 , 106 , 107 ). Activation of the ERK1/2 pathway by HA : RHAMM interaction increased tyrosine phosphorylation of FAK with a resultant increase in FA turnover and consequently cell migration ( 46 , 47 ).…”
Section: Role Of Rhamm In Oncogenesismentioning
confidence: 99%
“…Gain of function of paxillin has been linked with a variety of malignancies, 98 including melanoma, as it participates in adhesion and migration of the malignant cells. 99 There is indication that DUSP3 suppresses paxillin's activity through direct dephosphorylation or impairment of the FAK-paxillin interaction via the pathways mentioned above. 96 Nevertheless, additional studies are necessary for clarifying the exact relationship between FAK and paxillin.…”
Section: Paxillin-related Mechanismsmentioning
confidence: 99%